Detection of Metasploit Attacks Using RAM Forensic on Proprietary Operating Systems - Prakoso, Danar Cahyo; Riadi, Imam; Prayudi, Yudi (Universitas Muhammadiyah Malang, 2020)
Information technology has become an essential thing in the digital era as it is today. With the support of computer networks, information technology is used as a medium for exchanging data and information. Much information is confidential. Therefore, security is also essential. Metasploit is one of the frameworks commonly used by penetration testers to audit or test the security of a computer system legally, but it does not rule out the possibility that Metasploit can also be used for crime. For this reason, it is necessary to carry out a digital forensic process to uncover these crimes. In this study, a simulation of attacks on Windows 10 will be carried out with Metasploit. Then the digital forensics process uses live forensics techniques on computer RAM, where the computer RAM contains information about the processes running on the computer. The live forensic technique is important because information on RAM will be lost if the computer is off. This research will use FTK Imager, Dumpit, and Magnet RAM Capture as the RAM acquisition tool and Volatility as the analysis tool. The results of the research have successfully shown that the live forensics technique in RAM is able to obtain digital evidence in the form of an attacker's IP, evidence of exploits/Trojans, processes running on RAM, operating system profiles used and the location of the exploits/Trojan when executed by the victim.